Implementasi Metode Bit Plane Complexity Segmentation pada Citra Digital dalam Penyembunyian Pesan Rahasia - Z, Habibi (LPPM UNIKA Santo Thomas Medan, 2018)
Tapping secret message information often occurs in communication media. Safeguarding information or data distributed is very important to maintain confidentiality, integrity and authenticity. In steganography, there are several digital media that can be used as covers to hide the existence of a message, such as: Image, Audio, Text, and Video. The cover media research used in digital imagery is the Bit-Plane Complexity Segmentation Method. Bit-plane complexity segmentation (BPCS) is a steganography technique that has a large capacity, because it can hold confidential data with a relatively large capacity when compared to other steganography methods. It is expected that this research can minimize the leakage of important information that is very confidential and detrimental if it is known by others.